Impact of Investment Decisions, Capital Structure, and Firm Size on Profitability and Sustainable Growth, Moderated by Financial Flexibility in Construction Firms - Bela Septiana; Tri Ratnawati; Ida Ayu Sri Brahmayanti (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the effect of investment decisions, capital structure, company size on profitability and Sustainable Growth, with profitability as a mediating variable and Financial Flexibility as a moderating variable. Data is obtained from secondary sources, namely audited financial reports from heavy construction and civil engineering subsector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The analysis was carried out using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results showed that investment decisions, capital structure, and company size have a significant effect on profitability. However, only company size has a significant effect on Sustainable Growth. Investment decisions and capital structure have no significant effect on Sustainable Growth. Profitability also has an insignificant effect on Sustainable Growth and does not mediate the relationship between variables. In addition, financial flexibility does not moderate the relationship between profitability and sustainable growth. This finding indicates that increased profitability is more influenced by investment strategy, capital structure, and firm scale, but does not necessarily translate directly into Sustainable Growth.